Add to Cart!: Factors affecting Impulse Buying Behavior in E-Groceries - Patricia Isabel Cayabyab; Christina Louise Azcona; Fraince Erica Catama; Antonio Jr. Etrata (MEC-J (Management and Economics Journal), 2023)
The study analyzes the digital factors, namely Promotional Strategies, Motivation, Price, Website Quality, and Product Information, and their correlation and significant effect on Filipino consumers' online impulse buying behavior in e-groceries. Studies of online impulse buying behavior in e-groceries have yet to be explored in the Philippines. It is vital for e-grocery business owners and the e-grocery industry to gain insights on how to drive online impulsivity, leading to an increased profit and market share. The study used a quantitative approach, and online survey questionnaires were used to collect data through a 4-point Likert scale, avoiding neutral responses. The study targeted Generations Z and Y due to them being the dominant online shoppers in the Philippines. The study's findings were analyzed using Pearson Correlation which showed that all digital factors have a weak positive relationship with online impulse buying behavior. Additionally, the researchers conducted a Multiple Regression Analysis concluding that Website Quality, Motivation, and Promotional Strategies significantly affect online impulse buying behavior among e-grocery customers. However, other digital factors, namely Price and Product Information, were found to be insignificant. The result suggests that as e-grocery retailers boost their strategies pertaining to Website Quality, Motivation, and Promotional Strategies, a rise in online impulse buying can materialize.